Unlocking Gen Z Potential in Creative Industries: The Roles of Agile Leadership, Multifaceted Cooperation, Work Life Integration, and Mental Health - Mores, Harry; Pradipto, Yosef Dedy (Ilomata International Journal of Management, 2025)
This study introduces a novel integrative model that explains how agile leadership, multifaceted cooperation, and mental health support work together to sustain high performance among Generation Z employees in Indonesia’s digital creative agencies. As creative industry workplaces confront the challenge of engaging and retaining Gen Z talent, the findings show that flexible leadership and strong team collaboration not only improve performance to build resilient, high-performing teams in an era defined by change and generational transition. but also support the integration of personal and professional life for young workers. Importantly, mental health support amplifies the positive effects of agile leadership, highlighting the value of fostering psychologically supportive and adaptive work environments. By clarifying these relationships, the study offers actionable insights for creative agencies seeking.